RANCANGAN D-OPTIMAL UNTUK MODEL EKSPONENSIAL GENERAL - Tatik Widiharih; Sri Haryatmi; Gunardi Gunardi (MEDIA STATISTIKA, 2014)
Exponential model is widely used in biology, chemistry, pharmacokinetics and microbiology. D-optimal criteria is criteria with the purpuse to minimize the variance of  the estimator of parameters in the model. In this paper will discuss the D-optimal design for the generalized exponential model with  homoscedastics  errore assumtion. We used minimally supported design with the proportion of  each design point is uniform. The optimization is used  modified Newton, and the results obtained that the  design points are  interior points of the design region. Keywords: D-Optimal, Generalized Exponential, Minimally Supported Design, Support Point, Homoscedastics